2005
DOI: 10.1021/ac050490j
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Differentiation of Linear Peptides Composed of l-Amino Acids from Isomers Containing One d-Amino Acid Residue

Abstract: MS/MS of electrosprayed ions is shown to have the capacity to discriminate between peptides that differ by configuration about their alpha-carbons. It is not necessary for the peptides to possess tertiary structures that are affected by stereochemistry, since five epimers of the pentapeptide, H2N-Gly-Leu-Ser-Phe-Ala-OH (GLSFA) all display different collisionally activated dissociation (CAD) patterns of their protonated parent ions. The figure of merit, r, is a ratio of ratios of fragment ion abundances between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Bonferroni post hoc test is as follows: **, p Ͻ 0.01; ***, p Ͻ 0.001. experiment, and this difference can be manifested as different branching ratios among product ions. It has been shown that several different MS techniques can be used to probe this thermochemical difference between diastereomers (34,61,62,(72)(73)(74). We have also shown that simultaneous identification and characterization of potential DAACPs by MALDI-TOF/ TOF MS can be applied to distinguish D-isomer peptides in biological samples as small as individual neurons (38).…”
Section: Approaches For Identifying Daacps In Biological Tissuementioning
confidence: 91%
See 1 more Smart Citation
“…Bonferroni post hoc test is as follows: **, p Ͻ 0.01; ***, p Ͻ 0.001. experiment, and this difference can be manifested as different branching ratios among product ions. It has been shown that several different MS techniques can be used to probe this thermochemical difference between diastereomers (34,61,62,(72)(73)(74). We have also shown that simultaneous identification and characterization of potential DAACPs by MALDI-TOF/ TOF MS can be applied to distinguish D-isomer peptides in biological samples as small as individual neurons (38).…”
Section: Approaches For Identifying Daacps In Biological Tissuementioning
confidence: 91%
“…Homology searches that exploited structural and functional similarities between prohormone sequences in other species (75) allowed us to generate a hypothesis for the existence of two Aplysia putative DAACPs encoding the prohormones GdFFD and YdAEFLa. Prior to MS characterization, we confirmed the expression and distribution of these prohormones in the CNS by molecular techniques and investigated their final gene products in isolated neurons using proven MALDI-TOF/TOF MS. We took advantage of the distinct fragmentation patterns that can arise between peptide epimers using both MALDI MS/MS-and LC-ESI MS/MSbased approaches (34,38,61,73,74) to distinguish DAACPs and their all L-peptide counterparts. Our identification of GdFFD in Aplysia, similar to achatin-I (GdFAD) in Achatina, validates our homology-based MS approach as being effective for identifying novel DAACPs in related animals.…”
Section: Approaches For Identifying Daacps In Biological Tissuementioning
confidence: 99%
“…Both electron capture dissociation (ECD) and CID have been used in the study of fragmentation of peptides containing damino acid substitutions [14,15]. According to these studies, it is the doubly charged protonated parent ions that exhibit the highest stereo chemical sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%
“…This was made possible because the presence of a d-residue induces a difference in the fragmentation pattern upon analysis [23]. Until our work described in the next paragraph, this phenomenon has been mostly analyzed after ionization of peptides by electrospray, such as in [24].…”
Section: D-amino Acid Detection and Quantification In Crustacean Peptmentioning
confidence: 99%